A statistical comparison of digital X-ray images for MTB patients - Rijal, Omar Mohd. (2005)
A common practice in medical diagnosis and patient management is the comparison of two chest radiographs images. The difference between two digital images at two time points is a measure of the effect of treatment on the patient. Two measures of similarity, the ordinary regression coefficients, RS2 and coefficients of determination for the Unreplicated linear functional relationship model (ULFR), RF2, are used to compare images for the particular case of Mycobacterium Tuberculosis (MTB). Our results suggest that a series of R2 values indicates gradual declining trends with values falling within a band. New patients with a series of R2 values falling within this band may be consider as making a good or acceptable recovery.